Perkembangan Pembiayaan PT Bank Syariah Indonesia Tbk (BSI) Dalam Mendorong Pertumbuhan UMKM - Sari, Widya Rarta; Andriani; Lita Nabbila, Faricha; Putri, Dewi Fatmala (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2023)
The purpose of writing is to determine the development of PT Bank Syariah Indonesia Tbk (BSI) financing in encouraging the growth of Micro, Small, and Medium Enterprises UMKM. The method applied in this research is a descriptive method with a qualitative descriptive research type, which utilizes a literature study approach. The data source used in this research is secondary data. The research results show that PT Bank Syariah Indonesia Tbk (BSI) gives a big priority to funding for the Micro, Small, and Medium Enterprises (UMKM) sector, which is a type of productive financing, namely IDR 41.91 trillion from the previous year in 2021 of IDR 39. 4 trillion. This is in line with the Indonesian Banking Architecture (API) framework, the pillars of which are to encourage a national banking structure through financial support for UMKM financing. However, if you look at the percentage development of PT Bank Syariah Indonesia Tbk (BSI) financing for UMKM, it has decreased, from 8.36% in 2021 to 6.37% in 2022. This shows that the financing channeled by bank mergers in PT Bank Syariah Indonesia Tbk (BSI) experienced a decline. Correspondingly, there are around 60 million UMKM in Indonesia. As many as 77.6 percent or 46.6 million of the 60 million UMKM have not had access to bank financing.